The Effect of Organizational Strategy and Infrastructure Management on the Performance of Vocational High School 27 and Vocational High School 1 in Central Jakarta - Barjen Barjen; Matin Matin; Bedjo Susanto (International Journal of Education, Information Technology, and Others, 2020)
The purpose of this study was to examine the effect of organizational strategy and infrastructure management on the performance of vocational high school teachers. Research using quantitative methods and research design using path analysis. The population of this study was 35 teachers of SMK 27 and SMK 1. This study found more of the following: 1. There was a positive direct effect on organizational strategy in improving performance; 2, there is a positive direct effect on the management of infrastructure suggestions on performance.